ASSESSING ADVANCED GEOTECHNICAL ENGINEERING STUDENTS’ PERFORMANCE AND COURSE ASSESSMENT PLANS (CAP) DURING COVID-19 PANDEMIC - Juhaizad Ahmad; Ng Kok Shien; Faizah Kamarudin; Masyitah Nujid; Ng Wen Kuan; Anas Ibrahim; Badrul Nizam Ismail (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The effects of COVID-19 on instruction and learning have been discussed in education. This study evaluates the students’ performance before, during, and after the COVID-19 Movement Control Order (MCO) in the Advanced Geotechnical Engineering course. The methodology consists of data analysis of students’ grades of Civil Engineering students in UiTM Penang throughout nine semesters, from March 2019 to October 2023. The semesters before COVID-19 are March 2019 and September 2019. When the MCO was announced in March 2020, all Teaching and learning were ordered to be conducted via Online Distance Learning (ODL). There was only one semester involved during the MCO, which was the semester of September 2020, since this course was not offered during the semester of March 2020. The semesters from March 2021 onwards are conducted physically after lifting the MCO. The findings show that the students’ performance drastically declined after the MCO. The Course Assessment Plan (CAP) was revised to better represent the computer modelling component. Then, good results were obtained. Many students can improve their CO (Course Outcomes) and PO (Programme Outcomes) attainment by excluding the final exam component in the assessment. The mean scores indicate that, on average, CO1-PO2 has the lowest performance, while CO3-PO12 has the highest average performance. The standard deviation reflects the variability of the scores. CO3-PO12 has the highest variability, indicating a wider range of student scores. In contrast, CO2-PO3 has the lowest variability. Overall, students’ performance on project-based learning assignments is better than final exam assessment based on the student’s grade in March 2023. It is preferable to practise the final exam assessment for foundational courses rather than the application course, which involves hands-on computer modelling. This will help the students to equip them with essential skills before entering the real working environment.